The Dirichlet Problem for Elliptic-Hyperbolic Equations of Keldysh Type - Otway, Thomas H.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
Partial differential equations of mixed elliptic-hyperbolic type arise in diverse areas of physics and geometry, including fluid and plasma dynamics, optics, cosmology, traffic engineering, projective geometry, geometric variational theory, and the theory of isometric embeddings. And yet even the linear theory of these equations is at a very early stage. This text examines various Dirichlet problems that can be formulated for Keldysh-type equations, one of the two main classes of linear elliptic-hyperbolic equations. Open boundary conditions (in which data are prescribed on only part of the boundary) and closed boundary conditions (in which data are prescribed on the entire boundary) are both considered. Emphasis is placed on the formulation of boundary conditions for which solutions can be shown to exist in an appropriate function space, and specific applications to plasma physics, optics, and analysis on projective spaces are discussed.
1 Introduction -- 2 Mathematical Preliminaries -- 3 The Equation of Cinquini-Cibrario -- 4 The Cold Plasma Model -- 5 Light near a Caustic -- 6 Projective Geometry.
Keywords: Mathematics; Differential equations, partial; Mathematics; Partial Differential Equations